A Discursive Narrative on Planning for Urban Heritage Conservation in Contemporary World Heritage Cities in Portugal - Cidre, Elisabete M. P. (European Spatial Research and Policy, 2015)
This article analyses the structure of heritage conservation in the national context of Portugal. It assesses the political context in which planning operates, and the place of conservation and heritage planning within the planning system. By exploring how heritage conservation discourses developed within the national planning framework it is possible to understand the emergence of conservation practices and to consider recommendations for improved efficiency. The World Heritage cities in Portugal inform this research, as its designation should stand for best historic practices, internationally recognized and thus also compliant to an internationally coherent approach towards conservation policies. The narrative unveils a regulatory legislative framework exposed in general considerations rhetorically formulated as policy, usually setting out objectives and requirements, but saying ‘very little about the methodologies to be followed in the preparation of the plans’ (Rosa Pires 2001, p. 185). The resulting overlapping and sometimes conflicting competences, aims and objectives, all at play in the management of the historic city, thus call for concerted strategies underpinned by appropriate organizational and institutional structures and consistent policy making, where inclusive participation of all key stakeholders involved is critical.